Analysis The Effect of Website Quality on User Satisfaction with The WebQual 4.0 Method and Importance-Performance Analysis (IPA) (Case Study: SPMB Sebelas Maret University's Website). Issue 1 (March 2021) - Utami, Indah Sri; Winarno; Setiadi, Haryono
Abstract: The digital era describes the presence of technology where everyone can exchange information so quickly by the internet. For an institution, a website has its own benefits, among others, as a media for promotion, presenting information, and providing online services. This study aims to evaluate and improve website performance by analyzing the quality of the Sebelas Maret University selection of new student admissions (SPMB) website by utilizing a combination of WebQual 4.0 and Importance Performance Analysis (IPA) methods. In its analysis, WebQual method looks at 3 main dimensions: Usability Quality, Information Quality, and Service Interaction Quality. This research, which involved students in UNS, found that the website's gap analysis still has a negative value on all attributes and there are several attributes that require improvement related to website design, presentation of detailed and up-to-date information and navigation on the website. The results from this study are expected could be used as evaluation for the SPMB website's development to meet user expectation.